Misallocation and the Recovery of Manufacturing TFP After a Financial Crisis - Kaiji Chen; Alfonso Irarrazabal (Norges Bank, 2013)
The Chilean economy experienced a decade of sustained growth in aggregate out-put and productivity after the 1982 financial crisis. This paper analyzes the effects of resource misallocation on total factor productivity (TFP) of the manufacturing sector by applying the methodology of Hsieh and Klenow (2009) to the establishment data from the Chilean manufacturing census. We find that a reduction in resource misallocation accounts for about 46 percent of the growth in manufacturing TFP between 1983 and 1996. The improvement in allocative efficiency, moreover, is essentially driven by a reduction in the cross-sectional dispersion of output distortion. In particular, a reduction in the least productive plants.output subsidies is the most important reason for the reduction in resource misallocation during this period.
hdl:11250/2496710
Keywords: O11; O47; 330; TFP; Chile; total factor productivity; misallocation